KLAUSUL BAKU PADA TIKET BADAN USAHA ANGKUTAN UDARA NIAGA BERJADWAL (Studi Kasus PT. Lion Mentari Airlines) - , NOVIAN LISTIYOKO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Standard contract or provisions (agreement) printed on scheduled air carrier ticket unilaterally made by air carrier corporation, which impose the only two options for the passenger: âagreeâ or âdisagreeâ towards the contain of the agreement. This can prejudice the passenger if there is any burdensome provision which included on the ticket and unilaterally limit or even eliminate the air carriersâ responsibilities. In this research, the writer would like to create a research on the implementation of aviation regulations and consumer protection law and Indonesian Civil Code related with the assurance of passengers rights and specifically analyse the standard contract on Lion Air ticket. The method of this research is empirical research stressing on literature study to gain secondary data from legal materials. The writer also analyse the provisions and regulations related with standard contract, consumer protection, passengersâ rights and obligations as well as air carriersâ. Facts found on the research are the aviation regulations do not provide enough assurance on the passangers rights, which had been shown on air carriersâ responsibities on the compensation of lost baggage, flight delays and flight cancellation. On the other hand, had been noticed some clauses on Lion Air ticket standard contract, such as transfer of responsibility, refusal to carry passenger with special needs and clause of the amount of compensation.